High school personality traits and 48-year all-cause mortality risk: results from a national sample of 26 845 baby boomers. Issue 2 (20th November 2018) - Chapman, Benjamin P; Huang, Alison; Horner, Elizabeth; Peters, Kelly; Sempeles, Ellena; Roberts, Brent; Lapham, Susan
Abstract : Background: It is unclear if adolescent personality predicts mortality into late life, independent of adolescent socioeconomic status (SES). Methods: Over 26 000 members of Project Talent, a US population cohort of high school students, completed a survey including 10 personality scales and SES in 1960. Multi-source mortality follow-up obtained vital status data through an average 48-year period ending in 2009. Cox proportional hazard models examined the relative risk associated with personality traits, as well as confounding by both a measure of SES and by race/ethnicity. Results: Adjusted for sex and grade, higher levels of vigour, calm, culture, maturity and social sensitivity in high school were associated with reduced mortality risk (HRs=0.92 to. 96), while higher levels of impulsivity were associated with greater mortality risk. Further adjustment for SES and school racial/ethnic composition mildly attenuated (eg, 12%), but did not eliminate these associations. Final HRs for a 1 SD change in personality traits were similar to that for a 1 SD change in SES. Conclusions: Adaptive personality traits in high school are associated with all-cause mortality in the USA as far into the future as the seventh decade, and to a degree similar to high school socioeconomic disadvantage.